Slope Geometry Design Optimization in the Final Wall Pit Area of Sijebi PT. Solusi Bangun Indonesia Tbk, Narogong Factory, Bogor Regency - Afwach, Atina -; Najib, Najib -; Santi, Narulita (Jurnal IPTEK, 2024)
Slope design is an important component that must be considered in open-pit mining. It affects mine safety as well as the maximization of mining activities. These two things have an inversely proportional relationship and must be optimized with each other. This research aims to provide optimal recommendations related to geometry design that considers the stability of slope mining. The methods utilized in this research are Rock Mass Rating (RMR), Geological Strength Index (GSI), Slope Mass Rating (SMR), kinematics analysis, and limit equilibrium method. Based on the investigation that has been carried out, it is known that the value of the safety factor on the research slope is 4.192 for natural conditions and 3.967 for water-saturated slopes. The slope's safety value factor is known to be a very safe condition. Maximizing the mine design is crucial to achieving optimal extraction of mining materials. The most appropriate slope geometry design for the specified research area requires a single slope angle of 80°, a height of 10 m, and a width of 3 m, resulting in an overall slope of 68°. According to the findings of this recommendation, the safety factor value obtained is 2.076 for natural conditions and 2.050 under water-saturated conditions.